Pregunta
upstudy study bank question image url

If Jane gives 18 beads to Doris, both of them will have the same numbe of beads. If Doris gives 12 beads to Jane, Doris will have half as man beads as Jane. How many beads does Jane have at first?

Ask by Vaughn Brewer. in Cambodia
Jan 13,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Jane initially has 108 beads.

Solución

Let's solve the problem step by step by setting up equations based on the information provided. 1. **Let:** - \( J \) = Initial number of beads Jane has. - \( D \) = Initial number of beads Doris has. 2. **First Scenario:** - Jane gives 18 beads to Doris. - **After the transaction:** - Jane has \( J - 18 \) beads. - Doris has \( D + 18 \) beads. - According to the problem, after this transaction, they have the same number of beads: \[ J - 18 = D + 18 \quad \text{(Equation 1)} \] 3. **Second Scenario:** - Doris gives 12 beads to Jane. - **After the transaction:** - Doris has \( D - 12 \) beads. - Jane has \( J + 12 \) beads. - According to the problem, Doris will have half as many beads as Jane: \[ D - 12 = \frac{1}{2}(J + 12) \quad \text{(Equation 2)} \] 4. **Solving the Equations:** - **From Equation 1:** \[ D = J - 18 - 18 = J - 36 \] - **Substitute \( D = J - 36 \) into Equation 2:** \[ (J - 36) - 12 = \frac{1}{2}(J + 12) \] \[ J - 48 = \frac{1}{2}J + 6 \] \[ J - \frac{1}{2}J = 6 + 48 \] \[ \frac{1}{2}J = 54 \] \[ J = 108 \] **Answer:** Jane initially has **108 beads**.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

Let's analyze the problem in a step-by-step manner to find out how many beads Jane has initially. Let \( J \) be the number of beads Jane has at first, and \( D \) be the number of beads Doris has at first. From the first condition, if Jane gives 18 beads to Doris, they both have the same number of beads: \[ J - 18 = D + 18 \] This simplifies to: \[ J - D = 36 \quad \text{(1)} \] From the second condition, if Doris gives 12 beads to Jane, Doris will have half as many beads as Jane: \[ D - 12 = \frac{1}{2}(J + 12) \] Multiplying everything by 2 to eliminate the fraction gives us: \[ 2(D - 12) = J + 12 \] Expanding and simplifying results in: \[ 2D - 24 = J + 12 \] Thus, \[ J - 2D = -36 \quad \text{(2)} \] Now we have a system of equations: 1. \( J - D = 36 \) 2. \( J - 2D = -36 \) We can solve this system. From equation (1), we can express \( J \): \[ J = D + 36 \] Substituting this into equation (2): \[ (D + 36) - 2D = -36 \] This simplifies to: \[ 36 - D = -36 \] Solving for \( D \): \[ D = 72 \] Now substitute \( D \) back into equation (1) to find \( J \): \[ J - 72 = 36 \] \[ J = 108 \] Therefore, Jane initially has **108 beads**.

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad